100 countries, 5000 ideas where to go, when to go, what to see, what to do - Maxa, Rudy.; National Geographic Society (U.S.). Book Division (Washington, DC National Geographic Society, 2011)
"100 Countries, 5000 Ideas highlights 100 must visit countries from Antarctica to Zimbabwe. This travel planner features more than 200 color images as well as detailed maps. The guide also contains specific charts and sections, disseminating important travel information such as climate, language, currency, and required travel documents"--Provided by publisher.
Includes bibliographical references and index.
Translation of: Géobook : 100 pays, 5000 idées.
Keywords: Travel -- Guidebooks